2017
DOI: 10.1039/c7ay01335c
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric sensor for highly sensitive and selective detection of copper ion

Abstract: Colorimetric detection of Cu2+based on the inhibiting effect of Cu2+on the reaction ofl-cysteine with the established probe Cy-NB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The authors also reported that the chemodosimeter has an association constant of 8.80×10 5 M −1 with detection limit of 5.53×10 −7 M, with a visual change in color. Colorimetric sensor consisting of L‐cysteine with a probe Cy‐NB is also found effective for copper detection with a distinct visual color change . The probe is selective for Cu 2+ and has a copper detection limit of 8.6 nM.…”
Section: Detection Of Copper By Sensing Technologymentioning
confidence: 99%
“…The authors also reported that the chemodosimeter has an association constant of 8.80×10 5 M −1 with detection limit of 5.53×10 −7 M, with a visual change in color. Colorimetric sensor consisting of L‐cysteine with a probe Cy‐NB is also found effective for copper detection with a distinct visual color change . The probe is selective for Cu 2+ and has a copper detection limit of 8.6 nM.…”
Section: Detection Of Copper By Sensing Technologymentioning
confidence: 99%
“…For example, of the 55 sensors mentioned above, only 14 sensors displayed naked-eye detection below 10 μM. 34 , 42 , 44 , 50 , 53 , 57 , 61 , 65 , 66 , 69 , 70 , 72 , 76 , 87 Furthermore, only three of the studies challenged copper sensing in the presence of a competing metal ion 34 , 61 , 70 and none challenged copper sensing in the presence of 10-fold excess competing metal to copper, which is achieved in this work.…”
Section: Introductionmentioning
confidence: 99%
“…They also often require pre-concentration and/or filtering of the analytes, which all together prevent on-site, real time detection or systematic analysis. Recently more suitable devices for low cost and on-site measurements have been developed based on both colorimetric (Gao et al, 2017) and fluorescence (Zhang et al, 2018;Liu et al, 2018) optical spectroscopies, electrochemical (Cinti et al, 2018) or photo-electrochemical (Wang et al, 2018) techniques combined with a metal-ligand to increase selectivity. However, most of these devices are limited in term of LOD to the nanomolar or picomolar range.…”
Section: Introductionmentioning
confidence: 99%